EFFECTIVENESS OF BUTTERFLY PEA ETHANOL EXTRACT ON DECREASING BLOOD GLUCOSE LEVELS OF MALE MICE - Erica Mega Valentine Simangunsong; Yessi Febriani; Muharni Saputri; Dina Arisa; Ghianti Zarqa Afifah (Jambura Journal of Health Sciences and Research, 2023)
Butterfly pea flower (Clitoria Ternatea L.) contains flavonoids, tannins, and triterpenoids, which contain flavonoid compounds that have the potential as antioxidants. Antioxidants can suppress beta cell apoptosis without changing the proliferation of pancreatic beta cells. Antioxidants can bind free radicals so that they can reduce insulin resistance. The novelty of this study was that it examined the effectiveness of ethanol extract from butterfly pea flowers on reducing alloxan-induced male mice blood glucose levels. This study aimed to determine the effectiveness of the ethanol extract of butterfly pea flowers in reducing alloxan-induced blood glucose levels. The study used an experimental method with 5 treatments on 25 mice, beginning with purposive collection and processing of sample plants, preparation of Simplicia powder, preparation of ethanol extract of butterfly pea flowers, characteristic testing, determination of total ash content, determination of acid insoluble ash content, determination of extract content. Soluble in water, determination of ethanol soluble extract content, determination of water content, phytochemical screening, testing of antidiabetic activity of butterfly pea flower extract induced by alloxan. The examination results contained a total ash content of 5.20%, an acid-insoluble ash content of 1.16%, a water-soluble essence content of 47.94%, and a water content of 3.29%. The results of the compounds in the ethanol extract of butterfly pea flowers are alkaloids, flavonoids, tannins, saponins, and steroids. The results of testing blood glucose levels of ethanol extract of butterfly pea flower (EEBT) at a dose of 200mg/kg bb were known to be effective in reducing blood glucose after being induced by alloxan 150mg/kg bb with glucose levels of 319mg/dL dropping to 104.93mg/dL. The conclusion of the ethanol extract of the butterfly pea flower shows that the butterfly pea flower is efficacious as a blood glucose lowering agent in alloxan-induced mice (Mus musculus).